Effects of music and natural science training on aggressive behavior. (October 2016) - Roden, Ingo; Zepf, Florian D.; Kreutz, Gunter; Grube, Dietmar; Bongard, Stephan
Abstract: Extended music lessons have been suggested to reduce stress responses, and to increase well-being in primary school children. We investigated this assumption with regard to the provocation of aggressive behavior in primary school children (N = 34; 7–8 years of age). A computerized modified version of the Point-Subtraction Aggression Game ('Stimulated Aggression by Virtual Opponent'; SAVO) was used in this sample. Self-report (Positive and Negative Affect Schedule, PANAS) and physiological measures including systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and saliva cortisol concentrations were recorded before, during, and after the SAVO task. For the following 18 months, one group of children received weekly sessions of extended instrumental music lessons (n = 14; music group), while a control group received natural science training (n = 20; control group). A set of repeated measures analyses of variance (ANOVAs) did not show any differences in physiological measures between groups. Moreover, only children in the control group, but not music children, showed a significant increase of reactive aggressive behavior after the SAVO task. These results suggest that music training positively modulates reactive aggressive behavior in primary school children. Highlights: Music training might positively modulates reactive aggressive behavior. Music training had no beneficial effects on cardiovascular stress responses. Neurohumoral stress responses were not affected by music training.